Method of Linguistic Research approach between AL-AKHFASH and AL-FARRAA in Quranic meaning. (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research attempts to reveal the methodology of Linguistic research between two great and contemporary scientist, one of which belongs to the Visual School، which is the shy I b n masﹶ a da، the moth important of the linguists of his time, and al- farraa understand  people of ku fa in Arabic after AL-ksaie.This research shows the foundation of Quranic studies and the methodology of research during the second and third centuries AH, and thus wecan conclude that contents of these books is a language related to reading and dialects and the issues of grammatical، morphological and interpretive.